2000
DOI: 10.1111/1467-8683.00191
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Determinants of UK Board Structure Before and After Cadbury

Abstract: This paper investigates the determinants of the board structure of non-financial firms prior to, and post, the implementation of the recommendations of the Cadbury Committee. It provides evidence that managerial entrenchment is reduced following Cadbury, with the power afforded to CEOs with high levels of stock ownership being significantly diminished following the imposition of new standards of`best practice' regarding board structure. However, in spite of considerable pressure for institutional investors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 4 publications
(4 reference statements)
5
40
0
5
Order By: Relevance
“…While a number of studies supported CEO duality, several others concluded otherwise; and an additional set of studies (Dalton et al 1998 andDahya 2004) did not reveal significant relationships between leadership structure and firm performance. To recap on the earlier theoretical discussion, the results provide support that duality does not affect firm performance (Dahya et al 1996;Laing & Weir 1999;Dedman 2000;Franks et al 2001;Rhoades et al 2001;Weir et al 2002;Higgs 2003;Leng 2004;Kao & Chen 2004;Xie et al 2003;Davidson et al 2005 andAbdul Rahman &Mohamed Ali 2006). Brickley, Coles, & Jarrell (1997) showed that CEO duality is not associated with inferior performance; while Baliga, Moyer, and Rao (1996) concluded that there are no discernible differences in performance that can be attributed to a firm's leadership structure.…”
Section: Literature Review and Hypothesessupporting
confidence: 55%
“…While a number of studies supported CEO duality, several others concluded otherwise; and an additional set of studies (Dalton et al 1998 andDahya 2004) did not reveal significant relationships between leadership structure and firm performance. To recap on the earlier theoretical discussion, the results provide support that duality does not affect firm performance (Dahya et al 1996;Laing & Weir 1999;Dedman 2000;Franks et al 2001;Rhoades et al 2001;Weir et al 2002;Higgs 2003;Leng 2004;Kao & Chen 2004;Xie et al 2003;Davidson et al 2005 andAbdul Rahman &Mohamed Ali 2006). Brickley, Coles, & Jarrell (1997) showed that CEO duality is not associated with inferior performance; while Baliga, Moyer, and Rao (1996) concluded that there are no discernible differences in performance that can be attributed to a firm's leadership structure.…”
Section: Literature Review and Hypothesessupporting
confidence: 55%
“…Large firms like BTC are subject to scrutiny and to greater political and regulatory pressure from external interests (Belkaoui & Karpik, 1989). Unlike small firms, large firms face scrutiny by the media and may suffer bad publicity, loss of business and the imposition of more regulations following non-compliance than smaller firms (Dedman, 2000). This may therefore explain why BTC complies more with best practice corporate governance principles than small firms like BIDPA.…”
Section: Descriptive Analysis Of Soesmentioning
confidence: 99%
“…for the US: Brickley, Coles, & Jarrell, 1997; for the UK: Dahya, Garcia, & van Bommel, 2009;Vafeas & Theodorou, 1998;and Weir et al, 2002). Moreover, Dedman (2000) finds that older CEOs with longer tenures and higher firm equity ownership are less likely to comply with the Code recommendation of splitting CEO-chair roles. Hence, while evidence on the link of duality with firm performance is mixed, duality appears to help entrench management, thus providing support for the Code recommendation of splitting the CEO and chair roles.…”
Section: Duality Governance and Firm Performancementioning
confidence: 99%
“…Boone et al, 2007;Hermalin & Weisbach, 1998), CEO shareholdings (higher shareholdings implying greater power, Boone et al, 2007;Core et al, 1999), and CEO age. Prior evidence shows that older CEOs tend to have higher equity ownership, longer tenures and are less likely to comply with the Code (Dedman, 2000). They are also more likely to fill the board seats with insiders (Boone et al, 2007;Hermalin & Weisbach, 1988;Linck et al, 2008).…”
Section: Antecedents and Consequences Of The Changes In The Board Govmentioning
confidence: 99%